Autoimmune response against tyrosinase induces depigmentation in C57BL/6 black mice. (16th November 2020) - Al Robaee, Ahmad A.; Alzolibani, Abdullateef A.; Rasheed, Zafar
Abstract: Regulation of melanogenesis by tyrosinase has now become an attractive approach for treatment of vitiligo but still the role of tyrosinase in the induction of depigmentation remains largely unexplored. This study was explored the role of tyrosinase in the induction of autoimmune depigmentation in C57BL/6 mice. Depigmentation was induced in C57BL/6 mice by tyrosinase immunization. Induced depigmentation was characterized by visual detection and was verified by histopathological analysis of lesional and non-lesinal skin biopsies. Moreover, induced depigmentation was re-validated by gene expression analysis of vitiligo-relevant genes by Taqman assays. Immunization of C57BL/6 mice by tyrosinase induces depigmentation on hairs as well as on skin. Immunoassays with Protein A-purified immune IgGs showed high titre antibodies against tyrosinase. Histopathological analysis showed that the total melanocytes were depleted from the basal layer of the epidermis and also from the dermis of depigmented lesions. The gene expression of vitiligo-relevant genes TYRP1, DCT, MLANA, MCIR, POMC, FOXJ2, CSNK1G3, SOX10, PMEL and KIT was significantly low in lesional skin as compared with non-lesional skin ( p < .05). In contrast, the mRNA expression of CASP3 and NFκB1 was significantly high in lesional skin of depigmented mice as compared with non-lesional skin ( p < .05). Furthermore, involvement of cellular immunity in depigmentation was confirmed by the reduction of CD4 + :CD8 + lymphocytes ratio. In conclusion, this study shows that the autoimmune response against tyrosinase induces depigmentation in black C57BL/6 mice. The data obtained from the lesional and non-lesional skin biopsies showed the same features as were reported in human vitiligo patients.